2020
DOI: 10.1021/acschembio.0c00112
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immune Recruiters: Tools to Gain Chemical Control Over Immune Recognition

Abstract: Unprecedented progress made in the treatment of cancer using the body’s own immune system has encouraged the development of synthetic molecule based immunotherapeutics. An emerging class of these compounds, called Antibody Recruiting Molecules (ARMs) or Antibody Engagers (AEs), functions by reversibly binding antibodies naturally present in human serum and recruiting these to cancer cells. The recruited antibodies then engage immune cells to form quaternary complexes that drive cancer erradication. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 22 publications
(30 reference statements)
2
51
0
Order By: Relevance
“…[40,42] Despite this fact, of the three main haptens, DNP has received the most attention in the context of design antibody recruiting molecules, likely due to the commercial availability of affinity maturated anti-DNP antibodies, including mouse and human monoclonals that bind DNP with much higher affinity than endogenous anti-DNP in human serum. [43] However, it is also worth noting that DNP is also prone to nonspecific binding to albumin [44] and to aromatic residues such as tryptophan in the antigen binding site of antibodies. [45,46] By varying the ABT and TBT, many different ARMs systems have been developed, acting against a broad variety of disease relevant targets, including viruses and virally infected cells, [47,48] bacteria [36,49,50] and cancer cells.…”
Section: Antibody-recruiting Moleculesmentioning
confidence: 99%
“…[40,42] Despite this fact, of the three main haptens, DNP has received the most attention in the context of design antibody recruiting molecules, likely due to the commercial availability of affinity maturated anti-DNP antibodies, including mouse and human monoclonals that bind DNP with much higher affinity than endogenous anti-DNP in human serum. [43] However, it is also worth noting that DNP is also prone to nonspecific binding to albumin [44] and to aromatic residues such as tryptophan in the antigen binding site of antibodies. [45,46] By varying the ABT and TBT, many different ARMs systems have been developed, acting against a broad variety of disease relevant targets, including viruses and virally infected cells, [47,48] bacteria [36,49,50] and cancer cells.…”
Section: Antibody-recruiting Moleculesmentioning
confidence: 99%
“…As association time increases, more noncovalent complexes appear to form on the probe surface, which cannot be removed during the dissociation step. We hypothesize this represents slow higher-avidity binding of antibody to the surface or slow nonspecific antibody aggregation on the probe surface (see supporting information in Lake et al, 2020). To account for this we determined NCIR F at each time point and used this value to correct for the true extent of the covalent reaction.…”
Section: Measure Streptavidin-targeting Cir (Cir1/cir4) Reaction Kinementioning
confidence: 99%
“…Finally, we describe how to employ antibody-dependent cellular phagocytosis (ADCP) assays (Basic Protocol 3, Alternate Protocol 2) to define the CIR mechanism of action and demonstrate its anticancer function. All CIRs investigated Lake et al (2020) are shown. CIR1/2/3/4 and NCIR5 are referenced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations